UiT Survey of Working Climate: Mapping Experiences of Gender-Based Discrimination at UiT The Arctic University of Norway - Brokjøb, Lise Gulli; Martiny, Sarah E. (Septentrio Reports, 2022)
This report from the Prestige Project aimed to contribute a psychological perspective on gender issues and inequality relating to work climate, gender stereotypes, and discrimination in academia. The report is divided into three sections. Section I gives a brief introduction to current issues of gender inequality both worldwide and in Norway. Section II proposes a psychological framework to account for some of these current issues, focusing particularly on uneven gender distributions in certain academic fields by integrating several social psychological theories. Section III applies this framework to the particular context at UiT with three research questions: Do female and male employees experience the work climate at UiT differently? Do female employees at UiT face more negative stereotypes and feel discriminated against because of their gender compared to male employees? Is gender-based discrimination particularly evident in fields in which women are underrepresented? These were examined by surveying and analysing UiT employees’ self-reported experiences of their work climate, gender discrimination, and gender stereotypes. We additionally explored whether these factors interacted with how employees perceived the gender distribution at their workplace. Some notable gender differences and interactions were found in experienced gender discrimination, concern about encountering or confirming gender stereotypes about one’s own gender, and in motivation to socially approach co-workers. There was also found some tentative interaction effect of the perceived gender distribution at one’s workplace, but only in women. The report discusses the current findings and their implications for both a Norwegian academic setting, as well as the wider topic of gender inequality in the workplace. The report concludes by providing recommendations for academic leaders on how to promote gender equality in the workplace, counteract the potential effects of gender discrimination, and on how to promote employee well-being.